Health-related Quality Of Life Among Hemodialysis Patients And Its Associated Factors: A Scoping Review - Zaharuddin Bujang; Abdul Rahman Ramdzan; Nicholas Tze Ping Pang; Amirah Azzeri; Hafiz Jaafar; Henkie Isahwan Ahmad Mulyadi Lai (Universiti Putra Malaysia, 2024)
Malaysian Journal of Medicine and Health Sciences, Volume 19 Issue (supp 20) Page (240–249)